Computer Aided Design of Non-toxic Antibacterial Peptides - Rondon-Villarreal, Paola; Pinzon-Reyes, Efrain (Current Topics in Medicinal Chemistry, 2018)
Antimicrobial resistance is increasing at an alarming rate and the number of new antibiotics developed and approved has decreased in the last decades, basically for economic and regulatory obstacles. Pathogenic bacteria that are resistant to multiple or all available antibiotics are isolated frequently. Hence, new antibacterial agents are urgently needed and antimicrobial peptides are being considered as a potential solution to this important threat. These molecules are small host defense proteins that are part of the immune systems of most living organisms such as plants, bacteria, invertebrates, vertebrates, and mammals. These peptides are found in those parts of organisms that are exposed to pathogens and they are active against multiple organisms such as virus, bacteria, and parasites, among others. This review shows different strategies in the computational design of new antibacterial peptides, the physicochemical properties that are considered as the most relevant for the antibacterial activity and toxicity, and it suggests guidelines in order to help in the finding of new non-toxic antibacterial peptides through the development of computational models.
Keywords: Mutations